2009
DOI: 10.1016/j.virol.2009.07.038
|View full text |Cite
|
Sign up to set email alerts
|

SARS-coronavirus spike S2 domain flanked by cysteine residues C822 and C833 is important for activation of membrane fusion

Abstract: The S2 domain of the coronavirus spike (S) protein is known to be responsible for mediating membrane fusion. In addition to a well-recognized cleavage site at the S1–S2 boundary, a second proteolytic cleavage site has been identified in the severe acute respiratory syndrome coronavirus (SARS-CoV) S2 domain (R797). C terminal to this S2 cleavage site is a conserved region flanked by cysteine residues C822 and C833. Here, we investigated the importance of this well conserved region for SARS-CoV S-mediated fusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 43 publications
3
71
0
3
Order By: Relevance
“…In addition, ACE2 and DPP4 receptor transfection allows for more efficient entry in poorly permissive cells lines, such as HEK-293T cells. The method is highly adaptable to other viral envelope glycoproteins and has been used extensively 48,49,50,51,52,53,55,56,57,58,59 , often to complement other assays like biochemical analyses or native virus infections.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ACE2 and DPP4 receptor transfection allows for more efficient entry in poorly permissive cells lines, such as HEK-293T cells. The method is highly adaptable to other viral envelope glycoproteins and has been used extensively 48,49,50,51,52,53,55,56,57,58,59 , often to complement other assays like biochemical analyses or native virus infections.…”
Section: Discussionmentioning
confidence: 99%
“…They also suggest that several regions within S2 could act in a concerted fashion to mediate the membrane fusion process. Further studies have been conducted taking a more functional approach and considering other criteria that define fusion peptides, such as proximity to a cleavage site and sequence conservation (Madu et al, 2009a(Madu et al, , 2009b. The starting point for these studies was the identification of a second cleavage site in the SARS-CoV S S2 domain called S2′ (at R 797 residue) (Belouzard et al, 2009).…”
Section: Locating the Coronavirus S Fusion Peptidementioning
confidence: 99%
“…More recently this domain has been subjected to extensive characterization by electron spin resonance (ESR) spectroscopy (along with CD spectroscopy) to show membrane ordering and the critical involvement of the LLF motif . Another mutagenesis study based on cell-cell fusion and pseudovirion infectivity assays has also found that a pair of highly conserved cysteines (C822 and C833) and the flanking residues D830 and L831 located C-terminally to the 798-815 region played a critical role for fusion (Madu et al, 2009a). The small sub-domain formed by the cysteine pair form a loop structure, a situation that is reminiscent to the avian sarcoma/leukosis virus subtype A in which a pair of cysteines flank the internal fusion peptide of the Env glycoprotein .…”
Section: Locating the Coronavirus S Fusion Peptidementioning
confidence: 99%
“…El coronavirus en su envoltura es rico en cisteína, y sus residuos deben estar intactos para su actividad viral. La cisteína contiene un grupo tiol o sulfhidrilo (-SH); muchos virus, entre ellos el coronavirus, requieren de estos grupos sulfhidrilo reducidos para la fusión y entrada celular 36 . Los grupos sulfhidrilo son vulnerables a la oxidación, y por tanto susceptibles al ozono dado su poder oxidante.…”
Section: Efectos Biológicosunclassified
“…En el paciente afectado por COVID-19 suele haber hipoxia, de modo que este beneficio oxigenante será muy beneficioso. Se ha sugerido que, en los leucocitos, puede mejorar la actividad fagocítica de los neutrófilos, dentro de los monocitos y linfocitos, el peróxido de hidrógeno es reconocido como un compuesto señalizador intracelular, capaz de activar una tirosín quinasa que fosforila al NF-B con la consecuente síntesis de diferentes proteínas 36 . El NF-B juega un papel clave en la regulación de la respuesta inmune debida a la infección y en la respuesta inflamatoria 37,38 .…”
Section: Efectos Biológicosunclassified